KEPATUHAN IBU HAMIL DALAM KONSUMSI TABLET FE DI WILAYAH KERJA UPTD PUSKESMAS TENAYAN RAYA - Fatma Nadia; Rika Mianna; Ahmad Mustolih (STIKes Al-Insyirah Pekanbaru, 2021)
Compliance pregnant women implement a recommendation health workers to consume tablet fe pregnancy.This behavior can be influenced by knowledge, attitudes and education level. This report aims to review the knowledge, attitudes and levels of compliance pregnant women in consume tablet fe in the work area UPTD Puskesmas Tenayan Raya. This research using design research cross sectional with respondents as much 89 pregnant women .Where taken as random sample of sampling. Data analyzed by test chi square using spss 16,0 with a singnifikan p <0,05. Research results obtained that is no link between knowledge (p value = 0,014 ), attitude ( p value = 0,031 and education ( p value = 0,046 ) of compliance pregnant women in consume fe.Conclusions obtained bahwasannya knowledge, attitudes and education level with links to conduct smoking students, that suggested to the health workers would motivate pregnant women as well as never in providing information about the importance of consume tablet fe against what they contain, these figures mortalitas and morbilitas on the reduced. Keywords : Knowledge, attitude, education, compliance consumption Fe